Prospective study on the association between serum amino acid profiles and depressive symptoms among the Japanese working population. - Takako Miki (Public Library of Science (PLoS), 2021)
Objective Accumulating evidence suggests that amino acids, particularly tryptophan and glutamate, play an important role in the pathology of depression, but prospective epidemiologic data on this issue is scarce. We examined the association between circulating amino acids and the risk of depressive symptoms in a Japanese working population. Methods Participants were 841 workers who were free from depressive symptoms and provided blood at baseline and completed 3-yr follow-up survey. 30 varieties of amino acid concentrations in serum were measured using liquid chromatography/mass spectrometry. Depressive symptoms were defined using the Center for Epidemiologic Studies Depression Scale. Logistic regression was used to calculate the odds ratios of depressive symptoms according to serum amino acids with adjustment for lifestyle factors. Results A total of 151 (18.0%) workers were newly identified as having depressive symptoms at the follow-up. Baseline tryptophan and glutamate concentrations in serum were not appreciably associated with the risk of depressive symptoms. Risk of depressive symptoms tended to increase with increasing arginine concentrations; the multivariable-adjusted odds ratio for the highest versus lowest tertile of serum arginine was 1.65 (95% confidence interval: 0.96-2.83; P for trend = 0.07). No clear association was found for other amino acids. Conclusions Results of the present study do not support a significant role of circulating amino acids in the development of depressive symptoms among Japanese.